2011
DOI: 10.2351/1.3589243
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of UV laser scribing process for light emitting diode sapphire wafers

Abstract: Billions of light emitting diodes ͑LEDs͒ are used today in traffic control, automotive headlights, flat panel display technology, mobile devices, back lighting, projection, and general illumination applications. With the dramatic growth in LEDs, manufacturers are looking for technologies to increase production yield and decrease cost. Sapphire wafer singulation into miniature dies is one of the critical steps used in blue LED manufacturing. Typical dicing techniques used in wafer singulation process include la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 7 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…olid-state ultraviolet (UV) lasers that employ frequency conversion are attractive for high-resolution inspection and advanced material processing. 1,2) CsLiB 6 O 10 (CLBO) is an excellent nonlinear optical crystal for generating high-power UV output with wavelengths below 300 nm. [3][4][5] For high-repetition-rate pulsed lasers with a wavelength of 266 nm, we have recently found that UV output degradation and beam distortion in CLBO occurred at a lower peak power density than the bulk laser-induced damage threshold (LIDT).…”
mentioning
confidence: 99%
“…olid-state ultraviolet (UV) lasers that employ frequency conversion are attractive for high-resolution inspection and advanced material processing. 1,2) CsLiB 6 O 10 (CLBO) is an excellent nonlinear optical crystal for generating high-power UV output with wavelengths below 300 nm. [3][4][5] For high-repetition-rate pulsed lasers with a wavelength of 266 nm, we have recently found that UV output degradation and beam distortion in CLBO occurred at a lower peak power density than the bulk laser-induced damage threshold (LIDT).…”
mentioning
confidence: 99%
“…An excellent example is a rollable AMOLED display fabricated by ink-jet printing and laser lift-off technology, which is very promising for manufacturing large-size flexible AMOLED [6]. Semiconductor industry applications such as wafer scribing and dicing [7], micromachining of GaN [8], and extreme ultraviolet photomask repair [9,10] also highly benefit from femtosecond UV laser development. Other fields of applications where femtosecond NUV and DUV sources are used and have huge potential are medical device processing [11], direct medical applications [12], glass processing [13] and laser-induced periodic surface structuring [14].…”
Section: Introductionmentioning
confidence: 99%
“…here is an increasing demand for high-power deep ultraviolet (UV) sources in industrial fields such as high-resolution inspection 1) and advanced material processing. [2][3][4][5] All-solid-state UV lasers based on frequency conversion are considered to be a promising tool due to their high reliability, low maintenance cost and compact size. The efficiency of the wavelength conversion greatly depends on the characteristics of the nonlinear optical crystal.…”
mentioning
confidence: 99%